(Mixed) Strategy in Oligopoly Pricing: Evidence from Gasoline Price Cycles Before and Under a Timing Regulation - Wang, Zhongmin (Journal of Political Economy, 2009)
This paper studies oligopoly firms' dynamic pricing strategies in a gasoline market before and after the introduction of a unique law that constrains firms to set price simultaneously and only once per day. The observed gasoline pricing behavior, both before and under the law, is well captured by the Edgeworth price cycle equilibrium in the Maskin and Tirole dynamic oligopoly model. My results highlight the importance of price commitment in tacit collusion. I also find evidence that the price leadership outcome under the law is better predicted by mixed strategies play than by alternative hypotheses. (c) 2009 by The University of Chicago. All rights reserved.